1989
DOI: 10.1016/0014-5793(89)81182-2
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of progesterone and prostaglandin E2 production by lipoxygenase metabolites of arachidonic acid

Abstract: The role of several lipoxygenase metabolites of arachidonic acid in the action of luteinizing homone-releasing hormone (LHRH) on ovarian hormone production was investigated. Like LHRH, treatment of rat granulosa cells with S-HETE, S-HPETE, 12-HETE, IS-HETE or l5-HPETE stimulated progesterone (P) and prostaglandin E, (PGE,) production. 12-HEPE was most potent and stimulated P and PGE, equally well. By contrast, S-HETE stimulated P better than PGE,, while IS-HETE was a potent stimulator of PGE, but not of P. Sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…8) is remarkably consistent with the following observations in the rat: 1) LHinduced PG production and ovulation seem to be mediated by progesterone production and interaction with a classical progesterone receptor [48], 2) LOX metabolites (leukotrienes) are produced earlier than COX products (PGs) during hCG-induced ovulation [49], 3) treatment of perfused ovaries with LOX inhibitor (NDGA) inhibits LH-dependent PG production and ovulation [12], and 4) certain LOX metabolites can induce PG production by ovarian granulosa cells [50]. These observations suggest that LH (progesterone)-dependent ovulation in rat follicles is mediated by LOX product-dependent synthesis of PGs.…”
Section: Ovulationmentioning
confidence: 96%
“…8) is remarkably consistent with the following observations in the rat: 1) LHinduced PG production and ovulation seem to be mediated by progesterone production and interaction with a classical progesterone receptor [48], 2) LOX metabolites (leukotrienes) are produced earlier than COX products (PGs) during hCG-induced ovulation [49], 3) treatment of perfused ovaries with LOX inhibitor (NDGA) inhibits LH-dependent PG production and ovulation [12], and 4) certain LOX metabolites can induce PG production by ovarian granulosa cells [50]. These observations suggest that LH (progesterone)-dependent ovulation in rat follicles is mediated by LOX product-dependent synthesis of PGs.…”
Section: Ovulationmentioning
confidence: 96%
“…Further, the inhibitory action of NDGA on progesterone output was reversed by both LTB 4 and 12-HETE. Previous studies have revealed an interaction between the LOX pathway and progesterone production in the mammalian ovary [18,19]. Our present results indicate that LOX metabolites, especially produced through the 12-LOX pathway, might play a role in the regulation of progesterone output by the human placenta.…”
mentioning
confidence: 58%
“…It has been reported that the LOX pathway is involved in progesterone production in the ovary [18,19]. However, there is little information about the involvement of the LOX pathway in the production of progesterone by the placenta and whether effects of LOX metabolites on HSD11B2 regulation might be mediated through effects on progesterone production.…”
Section: Introductionmentioning
confidence: 98%
“…Prostaglandin E-2 (PGE2) is a hormone-like lipid metabolite generated by arachidonic acid via cyclooxygenase catalysis (91). Ovarian cancer can enhance proliferation and invasion through the PGE2/nuclear factor-kappa B signaling pathway (92).…”
Section: Lipid Metabolismmentioning
confidence: 99%